Students' Evaluation of the Effectiveness of Open Access Journals in Accelerating Paper Completion - Anugradia, Nabila; Kruehong, Tugsina; Alvarez, Jaime Lara (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to analyze students' perceptions in depth regarding the benefits of open access journals in the process of completing students' final assignments. Methodology: This research method uses naturalistic qualitative to analyze students' perceptions of Open Access journals in completing their final assignments. Data were collected through in-depth interviews with 20 physics education students who use open access journals. This research instrument uses a semi-structured interview guide. Data analysis was carried out using thematic analysis. Main Findings: Open Access Journals accelerate the completion of students' final assignments through free, fast, and quality access to scientific literature. Students feel that these journals enhance research independence, enrich students' understanding of the research topic, and provide a global perspective. However, challenges such as variation in journal quality, limited access to full articles, and language barriers still exist. However, students can overcome these by using alternative platforms and being more selective in choosing journals. Novelty/Originality of this study: This study offers a new perspective on the contribution of Open Access journals in accelerating the completion of final assignments for students in developing countries, especially Indonesia, who face financial and information literacy constraints. This study highlights students' experiences in using Open Access journals, accessibility challenges, and solution strategies, providing applicable insights for the development of open access-based education policies.